Challenges and Opportunities of a Shared Medical Facility for the Training of Medical Students in Rivers State: Perspective of Stakeholders and the Medical Students - N. Mato, Christie; Cleopatra Uzosike, Tondor; Ijah, Rex Friday Ogoronte Alderton; Alali, Aloni Adolphus (British Journal of Healthcare and Medical Research, 2023)
Background: Teaching hospitals are known to manage complex health conditions and train medical students. This study aims to explore the experiences of medical students from different universities and stakeholders who share a teaching hospital facility in Rivers State in terms of challenges and opportunities, and to suggest ways of overcoming the challenges encountered. Materials and Methods: A qualitative phenomenological study design was employed for this research conducted in Port Harcourt among medical students and stakeholders from both the Rivers State University and PAMO University of Medical Sciences, using a purposive sampling method. There were in-depth interviews and focus group discussions, and data obtained was uploaded for analysis into ATLAS.ti version 8.4.24. Results: There was a total of 10 females and 14 males, comprising 2 management staff, 8 lecturers from the two universities who were also medical doctors and 14 medical students. The commonly shared facilities were lecture halls, clinics, wards, theatres, hospital space and time. Some challenges identified were space constraint, distance between the Universities and teaching hospital, limited exposure to calls and clinical practice and academic work load. Inter-university interactions emerged as the most common opportunity, followed by a win-win for the teaching hospital and universities. Some suggestions were made for improvement in sharing a facility. Conclusion: A report of the experiences with shared facilities for undergraduate medical education is presented in this study. It is hoped that the findings will assist medical educators and teaching hospital management to make necessary changes that will enhance medical education.